Effect of the EAFRD subsidies on greenhouse gas emissions in the European agriculture - Obregon, Diana Sofia; Fischer, Jakub, 1978-; Svirskyi, Volodymyr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This study aims to examine the impact of the European Agricultural Fund for Rural Development (EAFRD) payments on greenhouse gas (GHG) emissions in agriculture in the EU27 member states from 2013 to 2020, accounting for other variables such as Agricultural land, Fertilizer consumption GDP per capita and more. The study is particularly relevant in the context of the European Green Deal and the Paris Agreement, as it seeks to understand the extent to which EAFRD payments contribute to reducing emissions in agriculture. To achieve this objective, panel data from 2013 to 2020 was used, and a range of econometric techniques was employed to analyze the relationship between EAFRD payments and GHG emissions in agriculture across the EU27 member states. The analysis will involve estimating various econometric models including Pooled OLS regression, Fixed-effects model, and Random-effects model, aiming to identify the most suitable model that effectively captures the dynamics and significant factors influencing GHG emissions in agriculture. A fixed effect model with robust standard errors (the Arellano-Bond type standard errors) was chosen as the best method after different testing and evaluations. In addition to EAFRD payments, the selected model incorporated other key explanatory variables including fertilizer consumption, crop production index, agricultural land, and livestock production index. The study found that EAFRD payments have a significant negative impact on GHG emissions in EU27 agriculture. This suggests that the payments effectively contribute to emissions reduction.
Vedoucí práce: Jakub Fischer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: official statistics [obor dipl. práce]; diplomové práce; master's theses